Relationship of the Pregnancy, Stress Biomarkers and Embryonic Losses in Jaffrabadi Buffaloes during Summer Season - Borakhatariya, Devasee N; Singh, Vivek K; Karangiya, Vijay K; Vijyeta, Hardeep P; Vala, Karshan B; Padodara, Ramesh J (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The current study sought to explore the relationship between various pregnancy and stress-related biomarkers, and embryonic mortality  in Jaffrabadi buffaloes during summer season. A total of 24 multiparous Jaffarabadi buffaloes were subjected to Ovsynch estrus  synchronization and fixed time artificial insemination (FTAI) program, and pregnancy was ascertained by trans-rectal ultrasonography  on day 35, and reconfirmed by per rectal palpation on day 60 post-AI. The plasma levels of INF-τ and PGFM were recorded on days  14, 16, 18, and 20 post-AI, whereas the pregnancy specific protein-B (PSPB), heat shock protein 70 (HSP 70), and progesterone were  evaluated on days 20, 24, 27, 30, and 40 post-AI. The conception rates obtained were 33.34% (08/24) at 35 days and 16.67% (04/24) at  60 days post-AI, indicating that 50.00% of conceived animals experienced embryonic losses. The overall INF-τ level was significantly  (p
Keywords: Embryonic loss; Heat stress; Interferon-tau; PSPB; PGFM; Summer Season.